Assessment of the Relationship between Fear of Cancer Recurrence, Spiritual Well-Being, and Mental Health among Cancer Patients: A Cross-Sectional Study - Agoritsa Londoudi; Konstantinos Skampardonis; Victoria Alikari; Paraskevi-Maria Prapa; Aikaterini Toska; Maria Saridi; Maria Lavdaniti; Sofia Zyga; Evangelos C. Fradelos (MDPI AG, 2024)
The purpose of this study was to examine the relationship between fear of cancer recurrence, spiritual well-being, and mental health among cancer patients. The study involved 217 patients undergoing chemotherapy. Data were collected with the following instruments: a demographic and clinical information recording form, the fear of cancer recurrence inventory, the Athens insomnia scale, the FACIT-Sp-12 scale for the assessment of spirituality, and the HADS scale for the assessment of mental health. For statistical analysis, SPSS statistical software was used, with the significance threshold set at 0.05;andtl number, t-test, one-way ANOVA, and multiple regression tests were used. The sample consisted of 217 cancer patients with a mean age of 63.7 years (SD = 11.6 years), 39.2% male and 60.8% female. The minimum value on the scale of fear of cancer recurrence was 0 and the maximum was 33 points, with a mean value of 14.1 points (SD = 8.2 points). The hospital scale of anxiety and depression was correlated, both in the dimension of anxiety and in the dimension of depression, significantly and positively with the scale of fear of cancer recurrence. Thus, greater fear of recurrence was associated with greater anxiety and depression. On the contrary, the correlations of anxiety and depression with the dimensions and the overall chronic disease treatment rating scale were significant and negative. So, greater spiritual well-being, in each domain and overall, were associated with less anxiety and depression. Finally, less fear of cancer recurrence was associated with finding greater meaning in life, greater peace, and overall greater spiritual well-being. In summary, fear of cancer recurrence is a predictor of psychological distress in cancer patients. However, spirituality can prevent the development of mental illness and FCR.